Applications to Solid State Systems - Schulz-Baldes, Hermann; Stoiber, Tom (Springer, 2022)
This chapter is about the applications of the results in the earlier chapters to solid state systems. There are numerous new results, and furthermore new or at least improved arguments of statements that can be already be found in the literature. The overview in the Preface essentially only mentions two new results (the bulk-boundary correspondence for irrational edges and the existence of flat bands of edge states for chiral Hamiltonians with a pseudogap and non-vanishing weak invariants). As this chapter is rather long and contains much more than that, let us give a brief more detailed outline of its contents.
CRIS-Team Scopus Importer:2024-12-16